Adolescent pregnancy and completion of basic education: a study of young people in three state capital cities in Brazil A gravidez na adolescência e a conclusão da educação básica: um estudo entre jovens do Brasil - Maria da Conceição Chagas de Almeida; Estela M. L. Aquino (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
This study evaluated the association between adolescent pregnancy and the completion of basic education, mediated by macrosocial indicators. A cross-sectional household survey was conducted with individuals between the ages of 18 and 24 in three Brazilian cities. For the purposes of this study, individuals between the ages of 20 and 24 were selected from this sample survey that included 4,634 people. A total of 29.6% of the girls declared that they had become pregnant prior to reaching the age of 20, while 21.4% of the boys stated that they had made a girl pregnant in adolescence. Girls from households with a per capita family income of US$70 or less and who became pregnant at least once during adolescence were more likely to have not completed basic education; whereas from households with a per capita family income of US$70 or less, with parents who separated before the adolescent reached the age of 20 and that had made a partner pregnant prior reaching the age of 20 were more likely to have not completed basic education. It is vital that the school system provides girls and boys with guidance on sexuality and contraception and encourages them to remain in education. Esse estudo avaliou a associação entre a gravidez na adolescência e a conclusão da educação básica mediada por marcadores macrossociais. Um inquérito do tipo corte transversal foi realizado em 2001 com jovens de 18 a 24 anos de três capitais brasileiras. Dos 4.634 jovens entrevistados, selecionou-se aqueles que na época da entrevista encontravam-se com 20 a 24 anos. A gravidez antes dos 20 anos foi declarada por 29,6% das moças, e 21,4% dos rapazes mencionaram ter engravidado uma parceira na adolescência. As jovens com renda familiar per capita de até US$70, que engravidaram na adolescência ao menos uma vez, referiram mais freqüentemente não terem concluído a educação básica. Entre os homens, ter renda familiar per capita até US$70, ter pais separados antes dos 20 anos e ter engravidado uma parceira antes dos 20 anos, implica a maior chance de não concluir a educação básica. Cabe ao sistema escolar orientar os jovens quanto à sexualidade e à contracepção, mas também estimular a sua permanência na escola.